Infinitive in Lithuanian as a second language - Ramonaitė, Jogilė Teresa (Baltistica, 2017)
One of the most apparent features characteristic of learners who speak Lithuanian as a second language is their overuse of infinitive forms where such forms should not be used in Lithuanian. The analysis of the general sequence of acquisition of the Lithuanian verb system shows that the infinitive was used nearly evenly through the whole acquisition process, i. e. learners who had just started to speak Lithuanian used about the same amount of infinitive forms as the more advanced speakers. This paper analyses in detail the use of the infinitive form by the learners at different levels of acquisition, what functions and in what contexts the infinitive form performs, as well as any changes in the development. The analysis makes it evident that despite the quantitative similarity of the use of the infinitive forms in different varieties of acquisition, the use changes fundamentally in quality. Moreover, it becomes clear that even the speakers of the basic variety, who often use the infinitive as the base form of the verb and therefore also as a predicate instead of a finite form, never use the infinitive of the modal verbs in this fashion and their utterances in which the infinitive is used according to the target Lithuanian language system employ the construction of modal verbs + infinitive. The paper also analyses what other constructions with the infinitive are used, when and in what way they start being used in the post-basic variety of acquisition.